2017
DOI: 10.1007/s11095-017-2193-4
|View full text |Cite
|
Sign up to set email alerts
|

A Two-way Randomized Cross-over Pharmacokinetic and Pharmacodynamic Study of an Innovative Oral Solution of Midazolam (ADV6209)

Abstract: Cyclodextrins have little impact on midazolam oral bioavailability and the pharmacokinetics parameters of midazolam formulation ADV6209 are close to those reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Oral formulations of midazolam, including Ozalin, have a rapid onset and short duration of action [1,21,22]. For example, in a study in 12 healthy adults [22], a sedative effect was observed ≈ 30 min after administration of a single dose of Ozalin 5 mg and lasted for ≈ 50 min. Maximum mean sedation levels occured 0.5-1 h post-administration, with complete alertness in all individuals at 4 h post-administration [22].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Oral formulations of midazolam, including Ozalin, have a rapid onset and short duration of action [1,21,22]. For example, in a study in 12 healthy adults [22], a sedative effect was observed ≈ 30 min after administration of a single dose of Ozalin 5 mg and lasted for ≈ 50 min. Maximum mean sedation levels occured 0.5-1 h post-administration, with complete alertness in all individuals at 4 h post-administration [22].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
“…α-hydroxymidazolam) [23]. The model incorporated data from single-dose studies of midazolam in a total of 49 participants, including 12 healthy adults [22] and 37 paediatric patients (5 infants aged 0.5-2 years, 10 children aged 0.5-11 years and 12 adolescents aged 12-17 years) [23]. Overall, the pharmacokinetic values with Ozalin were close to those reported for extemporaneous oral midazolam solutions/syrups in previous studies in paediatric patients [24,25].…”
Section: Population Pharmacokinetic Modelmentioning
confidence: 99%
See 3 more Smart Citations